The Thermal and Mechanical Properties of Medium Chain-Length Polyhydroxyalkanoates Produced by Pseudomonas putida LS46 on Various Substrates - Dartiailh, Christopher; Blunt, Warren; Sharma, Parveen K.; Liu, Song; Cicek, Nazim; Levin, David B. (Frontiers in Bioengineering and Biotechnology, 2021)
Medium chain-length polyhydroxyalkanoates (mcl-PHA) were produced by Pseudomonas putida LS46 cultured with a variety of carbohydrate and fatty acid substrates. The monomer compositions and molecular weights of the polymers varied greatly and was dependent on whether the substrate was metabolized via the fatty acid degradation or the de novo fatty acid synthesis pathways. The highest molecular weights were obtained from medium chain-length fatty acids, whereas low molecular weights were obtained from longer chain-length and more unsaturated fatty acids or carbohydrates. The differences in monomer compositions and molecular weights due to the choice of substrate did not affect the polymer thermal degradation point. The glass transition temperatures varied from -39.4 °C to -52.7 °C. The melting points, when observed, ranged from 43.2 °C to 51.2 °C. However, a profound substrate effect was observed on the crystallinity of these polymers. Reduced crystallinity was observed when the monomer compositions deviated away from C8-C10 monomer lengths. The highest crystallinity was observed from medium chain-length fatty acids, which resulted in polymers with the highest tensile strength. The polymer produced from octanoic acid exhibited the highest tensile strength of 4.3 MPa with an elongation-at-break of 162%, whereas the polymers produced from unsaturated, long-chain fatty acids remained amorphous. A comparative analysis of the substrate effect on the physical-mechanical and thermal properties of mcl-PHAs better clarifies the relationship between the monomer composition and their potential applications, and also aids to direct future PHA synthesis research towards properties of interest.